Letter (copy) : Spanish refugees - Tewson, Vincent
027-0007-001 Secretary's HVT/KA/388 23th September 1940 Mr. F. Hopcroft, Brentford & Chiswick Trades Council, 7 Brentwick Gardens, Brentford, Middx. Dear Mr. Hopcroft, SPANISH REFUGEES I have your letter of the 18th instant enclosing correspondence in regard to the above matter. So far as the General Council are concerned, they are closely connected with the work of the Basque Children's Committee, and we are spending a very large sum of money on the weekly maintenance of a large number of Spanish seamen in this country. In connection with the scheme for a National Labour Force, the position of the Spanish refugees will be taken into account. As you request I am returning the correspondence you sent with your letter. Yours sincerely, [Assistant Secretary] 292/946/27/7